Association between conventional and computerized sperm quality parameters with flow cytometric evaluation of frozen bovine semen - Varela, Elizabeth (2020)
The aim of this study was to evaluate the association between conventional and computerized parameters of seminal quality by flow cytometry of frozen bovine semen. Semen of 10 ejaculates from five bulls was frozen. Total motility (TM), progressive motility (PM), linear velocity (VSL), curvilinear velocity (VCL) and average path velocity (VAP) in thawed semen were evaluated using the SCA® system. Normal morphology (NM), sperm vitality (SV) and functional membrane integrity were assessed by the eosin-nigrosin stain and the hipoosmotic test (HOST). Mitochondrial membrane potential (∆ΨM) and membrane stability were assessed by flow cytometry through the DiOC6(3)/PI and M-540/Yopro-1 dyes, respectively. Pearson correlation coefficients were calculated, and multiple linear regression models were adjusted (p<0.05). Positive correlations between High-ΔΨM and Medium-ΔΨM with different conventional and computerized parameters of seminal quality were found (p<0.05). Likewise, positive correlation coefficients between the non-cryocapacitated non-apoptotic sperm population (M-Y-) and all the conventional and computerized parameters were found (p<0.05). Most regression coefficients for sperm populations with higher ΔΨM and membrane stability indicated significant increases in the quality of frozen-thawed semen (p<0.05). It is concluded that mitochondrial activity and membrane stability evaluated by flow cytometry are associated with the sperm quality estimated by conventional and computerized methods in cryopreserved bovine semen.